Development Sharia Investment During Covid-19 Pandemic - Asyraf Mustamin; Trimulato Trimulato (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
The development Islamic finance industry continues increase, with presence various Islamic financial products are increasingly varied. Islamic financial products are not only depositing funds in sharia banking but also developing investment products sharia financial institutions. Sharia investment can contribute economic recovery during Covid-19 pandemic. Determine development several sharia investment products and sharia financial institutions and to describe development sharia investment during Covid-19 pandemic. Orientation forms investment are intended for economic recovery affected pandemic. Type research used is library research qualitative method. Data source used is secondary data. Data obtained from has been presented institution, including data from Financial Services Authority (OJK), and from Directorate General Financing and Risk Management (DJPPR) Ministry Finance. Data obtained were then processed by researchers and then described. Data analysis technique used research is descriptive qualitative. Study show developments in Sharia investment products, Retail Sukuk, in 2019 experienced growth 13.15 percent, and savings Sukuk reached 8,436,570,000. For PeerToPeer (P2P) Sharia fintech institutions, assets in the April 2021 period grew 85.54 percent, and assets Islamic microfinance institutions grew 2.24 percent. Development sharia investment during Covid-19 pandemic through increased investment through digital technology. Sharia investment focuses economic recovery supports government activities. Sharia investment development Retail Sukuk (SR) and Savings Sukuk (ST), was transferred economic recovery. Maximum development sharia investment through sharia fintech for recovery sectors affected during Covid-19 pandemic. Development sharia investment through sharia financial institutions, increasing productive financing of SMEs. As well as development sharia investment based on investor profits and social needs sectors impacting Covid-19 pandemic.